2023
DOI: 10.1039/d2nr06343c
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective functionalization of in-plane nanoelectrode-antennas

Abstract: Stacked organic optoelectronic devices make use of electrode materials with different work functions, leading to efficient large area light emission. In contrast, lateral electrode arrangements offer the possibility to be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Interestingly, self-assembled monolayers (SAMs) enable adding new functionalities to a gold surface for building biosensors, 1,2 modulating the surface electric properties [3][4][5][6][7] and providing new perspectives for molecular devices. 8,9 Several reviews reported on the numerous studies devoted to the morphology of SAMs on various metals. [10][11][12] Among the interesting molecules, dodecanethiol has been investigated in detail and the corresponding SAMs arrange into a brush-like structure with the sulfur moiety strongly bound to gold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, self-assembled monolayers (SAMs) enable adding new functionalities to a gold surface for building biosensors, 1,2 modulating the surface electric properties [3][4][5][6][7] and providing new perspectives for molecular devices. 8,9 Several reviews reported on the numerous studies devoted to the morphology of SAMs on various metals. [10][11][12] Among the interesting molecules, dodecanethiol has been investigated in detail and the corresponding SAMs arrange into a brush-like structure with the sulfur moiety strongly bound to gold.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring values for the WF of functionalized surfaces has been carried out with various techniques: Ultraviolet Photoelectron Spectroscopy (UPS) under vacuum conditions, Kelvin Probe and more recently, Kelvin Probe Force Microscopy (KPFM) in atmosphere or in vacuum. 21,22,32,33 Knowing the WF is critical for devices, it has also been measured in various contexts including electric characterization of barrier heights in junctions, such as metal-organic interfaces, 8,9,21 lightemitting devices (LED), 6 or field emission guns. 34 For example, in the case of the most widely studied SAM, such as dodecanethiol on Au(111), the effective WF was measured mostly with UPS between 3.9 and 4.1 eV.…”
Section: Introductionmentioning
confidence: 99%